التأمين وأحكامه في فقه األأقليات المسلمة دراسة تحليلية في واقع مسلمي سريالنكا - Pulle Mohamed Abbas, Adam; Ghalia, Bouhedda (Al-Hikmah Research & Publication Center, 2020)
Sri Lanka muslims are minority citizens within about 10% of the total population; the country is currently experiencing sectarian unrest, which exposes the people and their wealth to continuous destruction without concern and probe in providing measures and means to protect them against these threat on their existence, and in the context of this reality, and a search for legislative means to prevent these destructions; This study aims to examine the issue of the legality of Muslim minorities' commitment to commercial insurance. Is it permissible for them to secure their money and their commercial stores in anticipation of attacks on them? What is the legal opinion on government, social, health and school insurance? The research explores four main issues in this study; the first is explanation of insurance and its types and the second is the presentation of the related juristic positions and their evidences from the commercial insurance ruling and the third topic dealing with the appropriate opinion in light of achieving the reality in general circumstances of the Muslim minority in general and in Sri Lanka in particular. The fourth topic touched on models in the applications of necessity in the permissibility of commercial insurance in the context of Sri Lanka. The study used based inductive method to identify the scientific material from its sources and references; and the analytical approach in the juristic opinions and comparison between its evidence and the analysis of the reality of the appropriate rule of law. The research concluded several results; the importance of adjudication rulings of "necessity" in order to preserve the Muslim minority in their religion, life and properties. Commercial insurance may be permitted, but with controls that define its scopes, and recommends that international insurance companies should expand their services to the Muslim minority countries. It also calls for activating social solidarity mechanisms such as: Zakat and endowments and efforts to establish investment funds. destructions; This study aims to examine the issue of the legality of Muslim minorities' commitment to commercial insurance. Is it permissible for them to secure their money and their commercial stores in anticipation of attacks on them? What is the legal opinion on government, social, health and school insurance? The research explores four main issues in this study; the first is explanation of insurance and its types and the second is the presentation of the related juristic positions and their evidences from the commercial insurance ruling and the third topic dealing with the appropriate opinion in light of achieving the reality in general circumstances of the Muslim minority in general and in Sri Lanka in particular. The fourth topic touched on models in the applications of necessity in the permissibility of commercial insurance in the context of Sri Lanka. The study used based inductive method to identify the scientific material from its sources and references; and the analytical approach in the juristic opinions and comparison between its evidence and the analysis of the reality of the appropriate rule of law. The research concluded several results; the importance of adjudication rulings of "necessity" in order to preserve the Muslim minority in their religion, life and properties. Commercial insurance may be permitted, but with controls that define its scopes, and recommends that international insurance companies should expand their services to the Muslim minority countries. It also calls for activating social solidarity mechanisms such as: Zakat and endowments and efforts to establish investment funds.